PENGUATAN PERLINDUNGAN ANAK DARI TINDAKAN HUMAN TRAFFICKING DI DAERAH PERBATASAN INDONESIA - Laurensius Arliman S (Jurnal Selat, 2016)
Kids are part of human who is not separated, all humans are from childhood. Protection of children are increasingly being discussed, as a result of the frequent violations of child protection cases in every region in Indonesia. In the border areas of Indonesia, many trafficked children. Therefore this paper tries to explain bagimana factors that cause the sale of children in border areas, how to organize the strengthening of the protection of children in border areas of Indonesia as well as how mewujdukan sustainable child protection in the border area. Apparently a lot of factors that led to the sale of children in border areas, especially poverty, in organizing the protection of children in the border area, it is necessary to strengthen the rule of law protecting children against trafficking, and to realize sustainable child protection to keep child life continuously. Keywords: Child, Human Trafficking, Regional, Border, Indonesia. Anak-anak adalah bagian dari manusia yang tidak terpisah, semua manusia berasal dari masa kanak-kanak. Perlindungan anak semakin banyak didiskusikan, akibat seringnya terjadi pelanggaran kasus perlindungan anak di setiap wilayah di Indonesia. Di daerah perbatasan Indonesia, banyak anak yang diperdagangkan. Oleh karena itu makalah ini mencoba menjelaskan bagimana faktor-faktor yang menyebabkan penjualan anak di daerah perbatasan, bagaimana mengorganisir penguatan perlindungan anak-anak di daerah perbatasan di Indonesia serta bagaimana mewujdukan perlindungan anak yang berkelanjutan di daerah perbatasan. Rupanya banyak faktor yang menyebabkan penjualan anak-anak di daerah perbatasan, terutama kemiskinan, dalam mengorganisir perlindungan anak-anak di daerah perbatasan, perlu memperkuat peraturan undang-undang yang melindungi anak-anak dari perdagangan manusia, dan untuk mewujudkan perlindungan anak yang berkelanjutan. Untuk menjaga kehidupan anak terus menerus. Kata kunci: Anak, Perdagangan Manusia, Daerah, Perbatasan, Indonesia.